Amentoflavone Impedes NF-κB Activation and Mediates Apoptosis Induction in Lung Cancer Cells: An in vitro and in silico exploration - Faiyaz SSM; Ahmad A; Fatima D; Shahid SMA; Kaushik G; Verma C; Tiwari RK; Kumar V (Journal of Inflammation Research, 2025)
Syed Shah Mohammed Faiyaz,1,2,* Afza Ahmad,3,* Daniya Fatima,4 Syed Monowar Alam Shahid,5 Gaurav Kaushik,6 Chaitenya Verma,7 Rohit Kumar Tiwari,8 Vinay Kumar9 1Department of Physiology, College of Medicine, University of Ha’il, Ha’il, 81451, Saudi Arabia; 2Department of Physiology, Radha Devi Jageshwari Memorial Medical College & Hospital, Muzzafarpur, Bihar- 844127, India; 3Department of Public Health, Dr. Giri Lal Gupta Institute of Public Health and Public Affairs, University of Lucknow, Lucknow, Uttar Pradesh, 226031, India; 4Department of Public Health, College of Public Health and Health Informatics, University of Ha’il, Ha’il, 81451, Saudi Arabia; 5Department of Biochemistry, College of Medicine, University of Ha’il, Ha’il, 81451, Saudi Arabia; 6Sharda School of Allied Health Sciences, Sharda University, Uttar Pradesh, 201310, India; 7Department of Biotechnology, Sharda University, Uttar Pradesh, 201310, India; 8Department of Clinical Research, Sharda School of Allied Health Sciences, Sharda University, Uttar Pradesh, 201310, India; 9College of Medicine, Pennsylvania State University Hershey Medical Center, Hershey, PA, 17033, USA*These authors contributed equally to this workCorrespondence: Rohit Kumar Tiwari, Department of Clinical Research, Sharda School of Allied Health Sciences, Sharda University, Gautam Buddha Nagar, Uttar Pradesh, 201310, India, Email rohit.tiwari1@sharda.ac.in Vinay Kumar, College of Medicine, Pennsylvania State University Hershey Medical Center, Hershey, PA, 17033, USA, Email vinayktyagi07@gmail.comContext: Lung carcinoma is a major contributor to cancer incidence and mortality worldwide. Chronic activation of NF-κB triggers activation of its target genes involved in promoting malignancy, metastasis, irregular proliferation of cells, and/or their resistance to programmed cell death. Amentoflavone (AMF) is a biflavonoid with intrinsic ability to modulate key signaling pathways associated with homeostatic and non-homeostatic conditions impels its exploration as therapeutic candidate against non-small cell lung carcinoma (NSCLC) A549 cells.Objective: This study investigates the anticancer potential of AMF in A549 cells, focusing on its unique dual role in NF-κB suppression and apoptosis induction, and compares its efficacy to the standard drug doxorubicin.Materials and Methods: A549 cells were treated with varying concentrations of AMF for 24 h. The effects of AMF on cell proliferation, oxidative stress, mitochondrial membrane potential, caspase activation, apoptosis, and NF-κB activation was analyzed.Results: A549 cell viability was substantially reduced (P < 0.001) at an AMF concentration of 60 μM. AMF exposure further increased nuclear fragmentation and condensation in A549 cells. AMF treatment induced apoptosis with concomitant augmentation intracellular production of reactive oxygen species (ROS), dissipation of mitochondrial membrane potential, and activation of the caspase cascade. Additionally, AMF mediated the inhibition of NF-κB and modulated the expression of NF-κB-associated genes involved in cell survival (Bcl-XL, Bcl-2, and survivin) and proliferation (cyclinD1). These results were further supported by in silico studies, which demonstrated a considerable binding energy score of AMF with NF-κB p65/50 compared with the standard drug (doxorubicin).Conclusion: Thus, it was concluded that AMF exerts potent anticancer effects in NSCLC A549 cells through dual mechanism such as direct inhibition of NF-κB signaling and apoptosis induction combined with its high binding affinity, positions it as a promising therapeutic candidate for NSCLC. Further preclinical studies are warranted to validate these findings.Keywords: anticancer, natural product, anti-inflammatory, lung cancer, apoptosis, caspases